1997
DOI: 10.1097/00000372-199708000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Lesions in Kaposi's Sarcoma: Case Report

Abstract: Bullous lesions have been only rarely described in Kaposi's sarcoma (KS), and their histopathologic features have never been described in detail. We report a case of bullous lesions of KS in an 82-year-old Italian woman. The patient had typical smooth pale reddish-grey slightly-raised KS plaques on the legs, present for at least 10 years. Several dull grayish-pink blisters (0.5 to 2 cm in diameter) affected both dorsa of her feet and ankles symmetrically. Two punch biopsies were taken, one from an infiltrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 7 publications
1
23
0
6
Order By: Relevance
“…Aggressive CKS in immunocompetent patients has been very rarely reported in the literature. 15,16 In addition, while the involvement of the head and neck is 40-67% in HIV infected patients, it has been reported in only 14% of cases with CKS. 17 Sikora et al suggested that even though most cases of KS are associated with immunodeficiency, clinical and laboratory proofs of this may remain inadequate; thus susceptibility to KS may be based on another unknown factor or inherited defect in host defence.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive CKS in immunocompetent patients has been very rarely reported in the literature. 15,16 In addition, while the involvement of the head and neck is 40-67% in HIV infected patients, it has been reported in only 14% of cases with CKS. 17 Sikora et al suggested that even though most cases of KS are associated with immunodeficiency, clinical and laboratory proofs of this may remain inadequate; thus susceptibility to KS may be based on another unknown factor or inherited defect in host defence.…”
Section: Figurementioning
confidence: 99%
“…14,15 Although, it was reported that bullae might be clinical hallmark of this type's histopathology, there are also another reports in which lymphoedematous type of KS histopathology had accompanied to marked lymphoedema clinically. 14,15,[18][19][20][21][22] The fourth case was interesting for very extensive lesions involving big sized plaques and also the existence of mucosal lesion. Clinical extensiveness and mucosal involvement may be unusual for a 5 years period of CKS in which a slow progression is anticipated.…”
Section: Figurementioning
confidence: 99%
“…PBS ile y›kand› ve protein blokaj› sonras›nda primer antikor ile ile oda s›cakl›¤›nda 1 saat inkübe edildi. S›ras›yla sekonder antikor, streptavidin peroksidaz kompleksi ve renklendirmek icin 6,[9][10][11][12][13][14][15][16] . En s›k görülen his- …”
Section: Giriflunclassified
“…Bu grupta yer alan olgular›n %26,4'ü makül, %37,6's› plak ve %36's› nodüler evre lezyonlard›r. Serimizde olgular›n %17,2'si histopatolojik özellikleri aç›s›n-dan literatürde tan›mlanan alt tipler ile uyum göstermekte-dir 6,[9][10][11][12][13][14][15][16] . En s›k görülen histolojik alt tip lenfanjiyektatik varyant (%7,3) olup, bunu s›ras›yla büllöz (%2,6), lenfanjiyom benzeri (%2,6), intravasküler (%2) ve piyojenik granülom benzeri (%2) varyantlar izlemektedir.…”
Section: Tart›flmaunclassified
See 1 more Smart Citation